Conceitos e legislaç\~ao sobre a agricultura familiar na América Latina e no Caribe - César Nunes de Castro (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– The concept of family farming has been disseminated since the 1990s throughout the world, including in Latin American countries and Brazil. Numerous official documents and academic papers make reference to the concept throughout the region. However, the use of related conceptual terminologies persists, such as, for example, peasant agriculture, or small-scale agriculture, among others. This article aims to analyze the existence and differences of this concept in Latin American and Caribbean countries. For the concept to be used within the scope of state action, it is necessary, that it is defined, unequivocally, in the form of law. As observed in this paper, this institutionalization is more evident in South American countries, less evident in Central America and practically absent in the Caribbean. At present, the authors weren't able to identify any form of consensus regarding the concept of family farming, and its legal acceptance, in the region. For the time being, Brazilian pioneering is evident in defining the concept and its applicability in public policies specifically aimed at family farmers.
Keywords: Q1; Q18; 330; family farming; concepts; laws; Latin America; Caribbean